The Ras-Raf pathway is activated in human immunodeficiency virus-infected monocytes and particpates in the activation of NF-kappa B. - Folgueira, L (1996)
Persistent human immunodeficiency virus (HIV) infection of human monocytes and macrophages increases I kappa B alpha degradation, resulting in the activation of NF-kappa B, a key transcription factor in the regulation of the HIV long terminal repeat. The signal transduction pathways leading to NF-kappa B activation in cells of the monocytic lineage, especially those regulated by HIV infection, and their relevance in regulating viral persistence remain unknown. Both p21ras and its downstream Raf-1 kinase participate in the transduction of signals initiated from a variety of cell surface receptors and in the regulation of transcription factors. We have studied whether the Ras-Raf pathway is functional and participates in HIV-mediated NF-kappa B activation in monocytic cells. Constitutively active p21ras (v-H-Ras) activated NF- kappa B-dependent transcription and induces the nuclear translocation of a bona fide p65/p50 heterodimer by targeting I kappa B alpha. In addition, the constitutively active form of Raf (RafBXB) also increases the NF-kappa B-dependent transcriptional activity. Because of the similarity between HIV and Ras-Raf-induced NF-kappa B activation in monocytic cells, we next tested whether HIV-induced NF-kappa B activation was mediated by the Ras-Raf signal transduction pathway. Negative dominant forms of both Ras (Ras N17) and Raf (Raf 301) decreased the HIV- but not lipopolysaccharide-dependent NF-kappa B activation in U937 cells. Moreover, Raf-1 kinase activity was greater in HIV-infected than uninfected monocytic cells in in vitro kinase assays. Altogether, these results indicate that the Ras-Raf pathway is unregulated in HIV monocytic cells and participates in the virus-induced activation of NF-kappa B.